Propagation of three native Brazilian Piper species by cuttings and indole butyric acid - Ferriani, Aurea Portes; Deschamps, Cícero; Amaral, Wanderlei do; Silva, Luiz Everson da (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Native Piper species present significant repellent, antimicrobial, inseticidal, anti-tumor and anti-protozoal biological activities. Studies on new species can discover unpublished potentialities and vegetative propagation for the development of cultivation protocols and reduce the natural extraction. The objective of this study was to evaluate the rooting of P. arboreum, P. cernuum and P. diospyrifolium stem cuttings with different treatments containing doses of indole butyric acid (0, 500; 1,000; 1,500; 2,000 and 3,000 mg L-1). Branches were collected in the “Bom Jesus Biological Reserve”, Parana state, Brazil. The cuttings, with a length of 12 cm and average diameter of 6 mm, were placed in 53 cm3 plastic tubes with the commercial substrate Tropstrato HP® and intermittent misting. After 90 days, the survival, mortality, cuttings with new shoots, number and length of the three main roots were evaluated. The percentages of rooting reached an average of 67.5% for P. arboreum, 51.6% for P. cernuum and 50.4% for P. diospyrifolium. A positive effect in the treatments containing the plant regulator was observed for rooting development, percentage of cuttings with shoots and number of roots per propagule, but there were variations in the responses of each species. Leaf retention was an important factor for the adventitious rooting formation in all evaluated species.